Development of bioethanol from bamboo shoots using Hydrogen Peroxide-Acetic Acid (HPAC) and Ultra High-Pressure Extraction (UHPE) Pre-treatment - Izz Qayyum; Nasrul Fikry Che Pa (Progress in Engineering Application and Technology, 2022)
Bamboo is an ideal feedstock for bioethanol production owing to its significantly faster growth rate and widespread and sustainable availability in the tropics. Gigantochloa albociliata is a Poaceae bamboo tree and shrub that produces bamboo shoots called rebung madu. Due to its natural abundance, high growth rate, perennial nature, and minimal maintenance needs, bamboo has the potential to be an exciting feedstock for advanced bioethanol production. To demonstrate biomass's potential for bioethanol production, pre-treated Gigantochloa albociliata bamboo shoots were examined as a feedstock for bioethanol production. The pre-treatment of biomass using Hydrogen Peroxide-Acetic Acid (HPAC) and Ultra High-Pressure Extraction (UHPE) reveals changes in the shape of the surface. The data indicate that the bamboo particles inflated, and the bamboo micropores widened. Thermal stability was determined for both native and treated biomass using a Thermogravimetric Analyzer (TGA), which revealed the existence of cellulose, hemicellulose, and lignin. After obtaining bioethanol from each native and treated sample, the absorbance and transmittance of the biomass samples were determined using ultraviolet-visible spectroscopy (UV-vis) and Fourier-transform infrared spectroscopy (FTIR). Each piece's spectra reveal the existence of ethanol peaks at 1060 to 1001 cm-1 and an absorbance of 550 nm. As a result of this study, it is anticipated that bamboo has a high potential for producing bioethanol with an effective pre-treatment process and the addition of raw material alternatives for bioethanol production.